Understanding mobile learning adoption in higher education: An empirical investigation in the context of the mobile library. Issue 5 (2nd October 2017) - Gan, Chunmei; Li, Hongxiu; Liu, Yong
Abstract : Purpose: This study aims to examine the factors driving an individual's behavioural intention to adopt mobile learning in higher education. Design/methodology/approach: Data were collected from university students in China via a survey. A total of 192 valid responses were collected. Structural equation modelling was used to assess the research model. Findings: The results show that both task and technology characteristics have significant impacts on task-technology fit (TTF), which in turn influences attitude. And attitude significantly affects behavioural intention. Regarding the factors, attitude was found to be the most influential predictor of mobile library adoption intention. In addition, the results provide strong support for the moderating effects of gender and experience on the relationship between TTF and behavioural intention. Originality/value: Extant research on mobile learning has mainly focused on investigating how user perceptions of mobile technology affect user adoption but has rarely considered the impact of TTF. This study attempts to fill this gap.